2015
DOI: 10.3791/52328
|View full text |Cite
|
Sign up to set email alerts
|

3D Modeling of the Lateral Ventricles and Histological Characterization of Periventricular Tissue in Humans and Mouse

Abstract: The ventricular system carries and circulates cerebral spinal fluid (CSF) and facilitates clearance of solutes and toxins from the brain. The functional units of the ventricles are ciliated epithelial cells termed ependymal cells, which line the ventricles and through ciliary action are capable of generating laminar flow of CSF at the ventricle surface. This monolayer of ependymal cells also provides barrier and filtration functions that promote exchange between brain interstitial fluids (ISF) and circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…3A,B). Semi-automated segmentation using ITK-SNAP (Shook et al, 2014;Snippert et al, 2010;Todd et al, 2017;Yushkevich et al, 2006) followed by 3D reconstruction of the lateral ventricles and whole brain using 3D Slicer (Acabchuk et al, 2015;Shook et al, 2014) revealed that the average total brain volume increases rapidly from 15 gw to 1 year. Regression analysis predicts that from 19 gw to birth, the brain grows at a nearly linear rate of 1.2×10 6 mm 3 /year (23 cm 3 /week) and from birth to 1 year at 5.5×10 5 mm 3 /year (11 cm 3 /week) (see also Kinoshita et al, 2001).…”
Section: Human Lateral Ventricle Volume and Surface Area Changes Corrmentioning
confidence: 99%
See 1 more Smart Citation
“…3A,B). Semi-automated segmentation using ITK-SNAP (Shook et al, 2014;Snippert et al, 2010;Todd et al, 2017;Yushkevich et al, 2006) followed by 3D reconstruction of the lateral ventricles and whole brain using 3D Slicer (Acabchuk et al, 2015;Shook et al, 2014) revealed that the average total brain volume increases rapidly from 15 gw to 1 year. Regression analysis predicts that from 19 gw to birth, the brain grows at a nearly linear rate of 1.2×10 6 mm 3 /year (23 cm 3 /week) and from birth to 1 year at 5.5×10 5 mm 3 /year (11 cm 3 /week) (see also Kinoshita et al, 2001).…”
Section: Human Lateral Ventricle Volume and Surface Area Changes Corrmentioning
confidence: 99%
“…Mouse brain tissue sections were stained with β-catenin overnight (rabbit polyclonal anti-β-catenin, 1:100; Cell Signaling Technology, #9562), secondary antibody for 1 h (donkey anti-rabbit 546, 1:500; Invitrogen, #A10040), nuclear stain DAPI (300 mM; Molecular Probes, #D-1306) for 10 min and imaged on a Zeiss Axio Imager M2 microscope with ApoTome (Carl Zeiss MicroImaging) with a Hamamatsu Photonics ORCA-R 2 digital camera (C10600). Alternating coronal sections were imaged, and the contours of the lateral ventricle walls and surface of the brain were traced to generate 3D reconstructions, as described (Acabchuk et al, 2015). Volume and surface area analysis were performed using StereoInvestigator and Neurolucida Explorer software (MBF Bioscience).…”
Section: Mouse Lateral Ventricle Reconstruction and Analysismentioning
confidence: 99%
“…Both datasets: Manual lateral ventricle ROIs were generated for all subjects using the subject T1-weighted structural MRI data and the ITK-SNAP (39) (itksnap.org) snake tool, following previously described guidelines for lateral ventricle extraction (40). The lateral ventricle ROIs were then eroded by two voxels (5.2 mm) using the erode function given by FSL's 'fslmaths' utility package (version 5.0.9) (36) in order to reduce partial volume effects of the surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral ventricle volumes were calculated based on the tracing protocol we developed and described previously [18]. Briefly, volumes were generated from serial coronal sections of the lateral ventricles, marked by S100β + ependymal cells that line the ventricles, traced in StereoInvestigator ® (MBF Bioscience, VT, USA) and then compiled in Neurolucida Explorer ® (MBF Bioscience), generating 3D volumetric renderings.…”
Section: Methodsmentioning
confidence: 99%